FAKTOR-FAKTOR PENYEBAB TINGGINYA CERAI GUGAT DI KABUPATEN SINTANG: Studi Perkara di Pengadilan Agama Sintang Tahun 2018-2021 - Lestari, Indah; Marluwi, Marluwi; Ulya, Nanda Himmatul (Al-Usroh, 2023)
The aims of this study are: 1) To find out the factors that cause the high rate of divorce in the Sintang Religious Court; 2) To find out the stages of handling a lawsuit for divorce in the Sintang Religious Court. This research uses qualitative methods, while the type of research used is empirical research that uses data in the field as the main data source. The data sources of this study used primary data sources, namely in the form of interviews with judges and clerks of the Sintang Religious Court whose subjects had been determined, then secondary data sources, namely from books, documents, journals and other data sources that could complement this research. The technique used in this research data collection is observation, interviews and documentation. The data collection techniques in this study were using interview guidelines, observation guidelines and smart phones. And the researcher's data analysis technique used data reduction, data exposure and drawing conclusions. Furthermore, the data validity technique is using triangulation techniques between data sources. Based on the analysis conducted by the researchers, it can be concluded that: 1) The factors that cause the high level of divorce in the Sintang Religious Court are due to continuous disputes and quarrels, leaving one party, economy, apostasy, domestic violence (domestic violence), gambling, drunk, sentenced to prison, disabled and forced marriage. However, among the factors above, the most dominant in the Sintang Religious Court is due to continuous disputes and quarrels between husbands. 2) The following are the stages of handling the divorce petition at the Sintang Religious Court, namely: reconciliation efforts, reading of the plaintiff's lawsuit, the defendant's answer, the defendant's reply, the defendant's duplicate, proof, the conclusions of the parties, the panel of judges' deliberation and the judge's decision.